ISLAM, LOCAL “STRONGMEN”, AND MULTI-TRACK DIPLOMACIES IN BUILDING RELIGIOUS HARMONY IN PAPUA (JOURNAL OF INDONESIAN ISLAM, 2020)
This paper comes with new perspectives in understanding the dynamics of Papuan society in relation to Islam and local “strongman”, especially in the frame of religious harmony. It enriches the research of how national political contestation affects the dynamics of religious harmony in Jayapura, Papua, through three important distinctions: first, socio-anthropological studies on how Islam and Muslim groups dynamics relate to the transformation of the society; second, the analysis of Islamic religious leaders’ roles in building religious harmony through local “strongman” perspective; third, the reframing of efforts in creating harmony in national, religious, and social life with multi-track diplomacies approach. This research with those three focuses results in a final lexicology: “building values/cultures does not mean tearing down entirely the existing ones; creating religious harmony does not need to eliminate teachings of any religions”. In other words, the process of assimilation, acculturation, and segregation at the most micro-level interactions, even individuals, has always to be recognized as an effort to create cultural amalgamation. In that way, local leaders of indigenous Papuans, bossism, and those who take refuge in cultural-structural organizations would never feel threatened with each other.